Enhancing the Early Inflammatory Response: The Role of Ozonated Aloe Vera Oil on IL-6 and TNF-α in Cutaneous Wound Repair - Gunawan, Evan Sebastian; Bernardus Parish Budiono (HM Publisher, 2025)
Background: Dysregulation of the initial inflammatory phase is a primary driver of impaired healing and the formation of chronic wounds, creating a critical need for therapies that can optimize this early response. This study tested the hypothesis that a novel formulation of ozonated aloe vera oil functions as a sophisticated bioregulator, promoting a beneficial, pro-regenerative inflammatory phenotype by transiently enhancing the host's innate repair signals. Methods: This was a preclinical, randomized, controlled study using fifty male Sprague-Dawley rats with 1 cm full-thickness excisional wounds. The therapeutic agent, ozonated aloe vera oil, was chemically characterized by its peroxide value (PV). Animals were randomized to receive topical treatment with either a positive control (aloe vera oil), a negative control (gentamicin ointment), or one of three graded doses of ozonated oil (Low PV, Medium PV, High PV). The primary outcomes, systemic (serum) and local (wound tissue homogenate) concentrations of Interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), were quantified by ELISA on days 3 and 7. Results: On day 3, all ozonated oil formulations induced a profound and significant upregulation of both local and systemic TNF-α and IL-6 compared to controls (p < 0.001). The topical treatment increased systemic TNF-α levels by over 40% and local tissue concentrations by over 60%. Critically, this pro-inflammatory surge was transient; by day 7, both local and systemic cytokine levels in all groups had returned to statistically indistinguishable baseline levels. Conclusion: Ozonated aloe vera oil acts as a potent, transient modulator of the wound microenvironment, enhancing the expression of key initiatory cytokines. This mechanism, likely mediated by the activation of redox-sensitive transcription factors, optimizes the crucial first phase of healing without inducing pathological chronic inflammation. This study supports a novel therapeutic paradigm aimed at enhancing, rather than suppressing, the body's innate capacity for repair.